Formative processes in Environmental Education: towards the maintenance or transformation of the reality? - Edileuza Dias de Queiroz; Patricia de Oliveira Plácido (Universidade Estadual Paulista Júlio de Mesquita Filho, 2015)
This work is the result of two master's degree researches completed by the Program of Postgraduate Studies in Education, Contemporary Contexts and Popular Demands of Federal Rural University of Rio de Janeiro. It aims to reflect and build some provocative considerations, although not inaugural on different formative processes of Environmental Education (EE) with regard to initial and continuing formation of educators. In the first study, it analyzes the incorporation of the environmental dimension in two degree courses of two public universities of Rio de Janeiro State, checking how EE is perceived and practiced by teachers. In the second, the approach rests on the analysis of formative procedures introduced by companies in the school environment. The theoretical-methodological option maintains the discussion in the historical and dialectical materialism, in the discourse analysis and in the practices of the educators involved in the researches. It concludes that in the formative processes of EE, the conservative discourses and practices are naturalized inside and outside of school. The formation of educators policies are built on the developmental logic, without critical depth, they are merely romanticized, technologic and behavioral experiments.